Peran Reforma Agraria Dalam Mewujudkan Ekonomi Berkelanjutan: Berdasarkan Perspektif Ekonomi Islam - Nadila, Nadila; Ghofur, Ruslan Abdul; Fasa, Muhammad Iqbal (Politeknik Piksi Ganesha Indonesia, 2025)
The agrarian reform program is a strategic instrument in creating social justice, welfare, equitable distribution of land ownership through two main pillars, namely agrarian reform and access reform. The purpose of this study is to analyze the role of agrarian reform in realizing a sustainable economy based on an Islamic economic perspective. This research uses a qualitative method with a literature study approach. The results show that the implementation of agrarian reform in West Tulang Bawang Regency has a positive impact on improving the welfare of the community, especially farmers and MSME actors. In Islam, agrarian reform is a form of mandate for natural resource management that must be carried out transparently, fairly, sustainably for the benefit of the people. The application of maqashid sharia principles is the main foundation in formulating agrarian policies that favor welfare. This research recommends institutional strengthening and community education for effective agrarian reform implementation..